MODEL ORGANISASI SEKRETARIAT DEWAN DALAM MENDUKUNG OPTIMALISASI FUNGSI DEWAN PERWAKILAN RAKYAT DAERAH (DPRD) DI PROVINSI LAMPUNG - Ginting, Arwanto Harimas; Tarigan, Meliasta Hapri (ipdn, 2020)
This study aims to offer a model of the organization of the secretariat of the council (setwan) at the provincial and district / city level capable of supporting the duties and functions of the DPRD in carrying out its duties. The organizational model is the result of a review of the existing organizational model combined with various literature reviews and adjustments to the facts that occur in the field. This study uses a qualitative method by collecting data from key informants and ordinary informants who were selected purposively and using interview, observation and questionnaire techniques. Data analysis with 2 (two) stages, triangulation, comparison of norms in force before explaining the results and findings. The results showed that the current organizational model has not been able to support the DPRD's main task in producing legal products in the form of regional regulations which are the initiative of the DPRD itself. The model offered from the research results will be able to improve the duties and functions of the DPRD in the future.